Moderating Role of Self-Esteem Between Perceived Organizational Support and Subjective Well-Being in Chinese Nurses: A Cross-Sectional Study - Yu, Mingli; Yang, Shihan; Qiu, Tian; Gao, Xuege; Wu, Hui (Frontiers in Psychology, 2019)
Purpose: Nurses are undertaking tremendous physical and psychological pressure, which may reduce their subjective well-being (SWB). This study is aimed to identify the relationship among perceived organizational support (POS), self-esteem and SWB, and to further explore whether self-esteem could be a moderator in the association between POS and SWB in Chinese nurses. Materials and methods: This study was conducted in Liaoning Province in China, in 2018. 606 valid questionnaires were collected. Demographic factors, job conditions, the Index of Well-Being, Survey of Perceived Organizational Support and Rosenberg’s Self Esteem Scale were included in each questionnaire. The association among POS, self-esteem and POS × self-esteem interaction with SWB were examined by hierarchical multiple regression analysis. The interaction was visualized by using simple slope analysis. Results: Average score of SWB in Chinese nurses was 8.27 ± 2.64. Being married was positively related to SWB, while having longer work time per week, having night shift and dissatisfied with nurse-patient relationship were correlated with lower SWB. POS and self-esteem were important factors for SWB. Self-esteem could moderate the relationship between POS and SWB. When self-esteem was higher, POS had a greater effect on SWB. Conclusions: SWB of nurses in the study was at a low level. Self-esteem could moderate the association between POS and SWB. More interventions related to POS and self-esteem will be helpful to improve SWB among nurses.